Development of Flipped Classroom Model with Differentiation Method (SQ3R) to Improve Critical Thinking Skills - Ilham Ibnu Firdaus; Ludfi Arya Wardana; Didit Yulian Krasdiyanto (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to develop an effective classroom teaching model using the SQ3R knowledge differentiation method and to test the validity of the product as well as the benefits of the model. The method used in this research is research and development (F&E) that follows the Borg & Gall model consisting of 10 steps, which includes the first trial, corrections based on the trial results, field test, and survey and distribution of the product to support education in schools. In the development stage, the products were tested for validity and effectiveness. The results showed that validation from experts obtained an average score of 9.7 with the category “very valid.” In addition, the 1-1 trial resulted in an average score of 93.63% for the learning model, 102% for the material aspect, 98% for practicality, and 96% for benefits. All aspects were categorized as “very interesting,” “very easy,” and “very useful.” Based on these findings, it can be concluded that the Flipped Classroom learning model with the SQ3R differentiation method is proven effective in improving critical thinking skills of grade IV students in science subjects at SDN Klenang Lor 1. This model is also very feasible to be applied in science learning and has the potential to be adapted and applied to other subjects at the elementary school level.